Educação infantil no município de Contagem - MG: análise de uma política (1996-2010) - Sandro Coelho Costa (2010)
The research has the main point to formulate the process of political public childish education in the Contagem-MG municipal, during the period of 1996-2010. We conducted a retrospective of childrens care in institutions of collective care and education, taking as a guide the year 1979, the year that we recorded the first organizations of daycare and preschools. We investigate the implementation of the right to education from a child of zero years old until six, in the last 14 years. We look for know and analyse the strategy, the principals, the conceptions and the proposal from the municipality public power to attend childhood education in that city. Regarding the methodologist instruments, we use in the empirical study the semi structured interview and documental analysis, highlighting the importance of statistical data. As theoretical framework we use a sociological approach, we identify the social actors and in what cultural context the policy was build, because, regarding the present childhood reality and the action of diferents actor (State, family and society) these politics can change during the year. Regarding this perspective, we highlight the working assumptions present in VIEIRA (2006). In parallel, we integrate in our references the contributions of "policy cycle approach," formulated by the English sociologist Stephen Ball and his colleagues (Bowe, Ball and Gold, 1992; Ball, 1994) to analyze the trajectory of social and educational policies. These theories have helped in our analysis of the establishment of policies for early childhood education in Contagem, highlighting the concepts, goals and social actors in the formulation and production of the texts. Used in this research study of public policy, grounded in the following authors: Easton (1970), Campbell (2002), Kingdon (2006), Muller and Surel (2002); English Ball (1994), Ball, Bowe, Ball, Gold (1992); Mainardes (2006). We demonstrated the following aspects of policies that understand the following analysis period: a) 1996 to 2002, after the enactment of LDBEN, we check some impacts of this legislation, policies directed to the training of professionals who worked in nurseries and preschools in the municipality; b) 2003 to 2004, we observed the first actions within the Department of Education regarding the transition of the covenants of nursery, until then under the management of Social Services; c) from 2005, with the entrance of the party of the Workers (PT) in the government, we register the design of a new scenario for early childhood education policies in Contagem: had an increased of financial investment, teaching, and as the first record of public service to children from zero to three years in educational institutions in the municipality.